UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR MENGGUNAKAN MODEL LEARNING CYCLE 5E PEMBELAJARAN IPA SISWA SEKOLAH DASAR - Agniya Ais Silviane; Khoimatun; Dede Hadiansah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the completion of student learning outcomes in science subjects that are not optimal, namely 83% of 25 students out of 30 students who have not completed. Because the teaching and learning process is more dominated by teachers, still using conventional learning models. One of the things that is done is to update the learning model that places students as the center of learning, namely by using the Learning Cycle 5E model. This study aims to determine the application of the Learning Cycle 5E learning model, to determine the improvement of science process skills and learning outcomes of class V students of UPTD SDN 1 Lajer. The research method used is Classroom Action Research (CAR) with 3 cycles and using the Kemmis & MC Taggart design model consisting of four steps and repetitions, namely: planning, implementation, observation and reflection. This research was conducted in class V of SD Negeri 1 Lajer totaling 30 students. The results of the application of science process skills in cycle I, cycle II, and singkus III increased gradually. The percentage of cycle I is 59% in the sufficient category, cycle II is 80% in the good category, and cycle III is 85% in the very good category. Student learning outcomes have increased. In cycle I, cycle II, and cycle III students met the learning completeness and increased in each cycle from 15 students with a percentage of 50% there was an increase to 22 students with a percentage of 73% then increased to 26 students with a percentage of 87%. This study shows that learning outcomes have reached the classical success indicator of 85%. Based on the results of the study, it shows that the Learning Cycle 5E model can improve science process skills and learning outcomes of fifth grade elementary school students.